Variability of Actinobacteria, a minor component of rumen microflora - Suľák, M; Sikorová, L; Jankuvová, J; Javorský, P; Pristaš, P (Folia microbiologica, 2012)
Actinobacteria (Actinomycetes) are a significant and interesting group of gram-positive bacteria. They are regular, though infrequent, members of the microbial life in the rumen and represent up to 3 % of total rumen bacteria; there is considerable lack of information about ecology and biology of rumen actinobacteria. During the characterization of variability of rumen treponemas using non-cultivation approach, we also noted the variability of rumen actinobacteria. By using Treponema-specific primers a specific 16S rRNA gene library was prepared from cow and sheep rumen total DNA. About 10 % of recombinant clones contained actinobacteria-like sequences. Phylogenetic analyses of 11 clones obtained showed the high variability of actinobacteria in the ruminant digestive system. While some sequences are nearly identical to known sequences of actinobacteria, we detected completely new clusters of actinobacteria-like sequences, representing probably new, as yet undiscovered, group of rumen Actinobacteria. Further research will be necessary for understanding their nature and functions in the rumen.
Keywords: bachor; Sheep; DNA bakterií; DNA, Ribosomal; Phylogeny; Actinobacteria; Molecular Sequence Data; molekulární sekvence - údaje; RNA ribozomální 16S; Rumen; zvířata; RNA, Ribosomal, 16S; DNA, Bacterial; Cattle; biodiverzita; fylogeneze; skot; ribozomální DNA; Animals; ovce; Biodiversity